Graphite Intended for Green Engineering Developed by Noncontaminant Reverse Abrasion - Roberto Baca Arroyo (Advances in Materials Science and Engineering)
Graphite intended for green engineering was synthesized by noncontaminant reverse abrasion, which consists of graphite layers assembled with thickness controlled on SiC sandpaper as insulating substrate. Phase formation of the graphite layers was validated by X-ray diffraction studies and its finished profile by Atomic Force Microscopy (AFM). Transport parameters of only three layers were evaluated from current-voltage curves. Mathematical functions such as derivative and modulation of a signal have been built by graphite circuits using different performance principles, compared to those used with silicon devices. The trends related to electronic engineering should be achieved with design of the graphite-based devices to facilitate their mass production in the near future.